Bacteriological profile in intubated and mechanically ventilated babies in NICU in Krishna Institue of Medical Sciences, Karad, Maharashtra, India - Menon, Shreya S.; Pawar, J. M. (International Journal of Contemporary Pediatrics, 2018)
Background: Infections are the most important and leading cause of mortality and morbidity among the patients admitted in ICU. Nosocomial infection is a critical issue among intubated patients which is responsible for significant morbidity and mortality of these patients. The objectives of this study were to characterize bacterial species from the respiratory tract of patients undergoing endotracheal intubation and to determine the sensitivity of organism to various antibiotics. To propose a suitable antibiotic therapy in intubated and mechanically ventilated babies according to cultures and antibiotic sensitivity obtained from ET tube of previously intubated and ventilated babies in NICU. Methods: It was a cross sectional descriptive study conducted in the NICU settings of KIMS, Karad, from January 2016 to June 2016. 78 neonates were intubated for more than 48 hours were included in the study during this duration, among which 44 were considered as cases. Results: Out of 44 samples,16 were sterile and 28 were positive for organisms.25 cases were started prophylactic antibiotics before intubation with inj. ampicillin and inj. gentamicin (27.3%), inj. piperacillin and inj. amikacin (15.9%), inj. vancomycin (9.1%), inj. meropenem (2.3%), of which 6 cases were sterile and 19 were positive for organisms. Antibiotic sensitivity to inj. colisitn (38.7%) followed by inj. tigecycline (13.6%), inj. levofloxacin (4.6%) and inj. tetracycline (2,3%) and inj. clindamycin (2.3%). In majority cases antibiotic sensitivity was obtained positive to 3 antibiotics. Conclusions: From the present study we have come to a conclusion that analyzing ET culture was important as the sensitivity to the antibiotics obtained was different from those given prophylactically as a protocol. Hence this study will help us in implementing different antibiotics prophylactically with regard to the commonly obtained sensitivity pattern.